Realisation and robustness evaluation of a blind spatial domain watermarking technique. Issue 4 (3rd April 2017) - Parah, Shabir A.; Sheikh, Javaid A.; Assad, Umer I.; Bhat, Ghulam M.
ABSTRACT: A blind digital image watermarking scheme based on spatial domain is presented and investigated in this paper. The watermark has been embedded in intermediate significant bit planes besides the least significant bit plane at the address locations determined by pseudorandom address vector (PAV). The watermark embedding using PAV makes it difficult for an adversary to locate the watermark and hence adds to security of the system. The scheme has been evaluated to ascertain the spatial locations that are robust to various image processing and geometric attacks JPEG compression, additive white Gaussian noise, salt and pepper noise, filtering and rotation. The experimental results obtained, reveal an interesting fact, that, for all the above mentioned attacks, other than rotation, higher the bit plane in which watermark is embedded more robust the system. Further, the perceptual quality of the watermarked images obtained in the proposed system has been compared with some state-of-art watermarking techniques. The proposed technique outperforms the techniques under comparison, even if compared with the worst case peak signal-to-noise ratio obtained in our scheme.